Over Ten Years of Experience with a Modified Right Atrial Anastomosis in Orthotopic Heart Transplantation: Follow-up and Comparison with the Biatrial and Bicaval Technique - Huenges, Katharina; Panholzer, Bernd; Fritzsche, Katharina; Broch, Ole; Renner, Jochen; Friedrich, Christine; Rahimi-Barfeh, Azizolah; Reinecke, Alexander; Cremer, Jochen; Haneya, Assad (The Thoracic and Cardiovascular Surgeon, 2018)
Background In 1997, a modified right atrial anastomosis (cavoatrial technique) for orthotopic heart transplantation (oHTx) was first developed in our institution. The purpose of this study is to report our long-term experience with this technique compared with biatrial and bicaval technique.Methods Retrospectively, 202 consecutive oHTx between 1997 and 2013 were analyzed. The applied transplantation techniques were biatrial (n = 108), bicaval (n = 22), and cavoatrial (n = 72).Results Demographic data were similar in all groups. The cardiopulmonary bypass and cross-clamp time were significantly shorter in the biatrial group. Follow-up echocardiographic examination showed excellent results in all groups with no relevant differences. After 1 year, occurrence of severe tricuspid regurgitation (biatrial 1.9% vs bicaval 0.0% vs cavoatrial 1.4%) was low in all groups. Rate of permanent pacemaker implantations was also low (12.0% vs 5.0% vs 11.1%). There were no significant differences in survival between the groups.Conclusion The cavoatrial technique can be a safe and simple alternative for heart transplantation. Easy handling and similar reduced postoperative complications encourage the use of this technique.
Keywords: heart failure; transplantation heart; cardiac